Food Shopping and Food Coping Strategy in Gen-Z College Students - Sinta Dewi Andayani, Ni Luh Nyoman; Budi Susrusa, Ketut; Korri Arisena , Gede Mekse; Bakhtiar, Ary (Faculty of Agriculture Udayana University, 2026)
BACKGROUND AND OBJECTIVES Gen-Z college students are in a transitional phase towards economic independence, making financial management a significant challenge, especially for food needs. Budget limitations and social influences, such as peer habits, often encourage students to choose cheap, less nutritious food, which can have a negative impact on their health and well -being. This study examines pocket money allocation patterns, food coping strategies, and the relationship between pocket money, spending, and food coping strategies. By understanding these dynamics, the research is expected to provide insights to support food security policies and improve student welfare. METHODS This research uses the library research method. Library study is a research approach conducted by collecting information and data from various literature sources relevant to the topic of food coping strategies and food expenditure of university students, such as documents, books, articles, journals, and other materials available in the library. FINDINGS Discover how economic and social factors affect the consumption patterns of university students in more depth by summarizing previous research results that contain data collected from several research locations and various research subjects with different economic and social backgrounds. This research was created to understand the food coping strategies applied by university students and is expected to play a role in developing policy recommendations to support student food security and improve student welfare. CONCLUSION This literature review shows that students' pocket money allocation is influenced by culture, lifestyle, and financial limitations, which impact their food and non-food consumption patterns. Students with limited pocket money tend to reduce food expenditur e using various coping strategies. Solutions can be implemented, including food subsidies, food aid, and financial literacy programs to help students manage their finances. However, further research is needed to assess these strategies' long-term impact and the policies' effectiveness in improving student welfare.